2015
DOI: 10.1186/s40781-015-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary copper on organ indexes, tissular Cu, Zn and Fe deposition and fur quality of growing-furring male mink (Mustela vison)

Abstract: The objectives of this study were to study the effects of different levels of dietary copper on organ indexes, tissular Cu, Zn and Fe deposition and fur quality of mink in the growing-furring periods. One hundred and five standard dark male mink were randomly assigned to seven groups with the following dietary treatments: basal diet with no supplemental Cu (Control); basal diet supplemented with either 6, 12, 24, 48, 96 and 192 mg/kg Cu from copper sulphate, respectively. The colour intensity scores displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although fur quality of fur-bearing animal is affected by many factors, mineral levels in the diet play a vital role. Other studies (Wu et al, 2014a(Wu et al, , 2015aLiu et al, 2016) have indicated supplementation with minerals such as Cu and Zn supplementation could improve the fur quality of mink and foxes. In the present study, there is was difference in guard hair length and underfur length among Zn treatments, suggesting that Zn concentration in the basal diet is sufficient for fur maturation in mink.…”
Section: Discussionmentioning
confidence: 99%
“…Although fur quality of fur-bearing animal is affected by many factors, mineral levels in the diet play a vital role. Other studies (Wu et al, 2014a(Wu et al, , 2015aLiu et al, 2016) have indicated supplementation with minerals such as Cu and Zn supplementation could improve the fur quality of mink and foxes. In the present study, there is was difference in guard hair length and underfur length among Zn treatments, suggesting that Zn concentration in the basal diet is sufficient for fur maturation in mink.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is involved in the synthesis of hemoglobin through its interaction with Fe, facilitating its intestinal absorption, release, and cellular utilization . It also participates in connective tissue formation, free radical removal, as well as hair production and pigmentation . Manganese is required for the synthesis of mucopolysaccharides through the polymerase and galacto-transferase enzymes and it is a component of arginase, pyruvate carboxylase, and mitochondrial superoxide dismutase .…”
Section: Introductionmentioning
confidence: 99%
“…4 It also participates in connective tissue formation, free radical removal, as well as hair production and pigmentation. 5 Manganese is required for the synthesis of mucopolysaccharides through the polymerase and galactotransferase enzymes and it is a component of arginase, pyruvate carboxylase, and mitochondrial superoxide dismutase. 6 Zinc is a constituent of hundreds of metalloenzymes, being involved in several functions, including protein and carbohydrate metabolism, nucleic acid synthesis, cell replication and differentiation stabilization of DNA, RNA, and ribosomes, immune response, skin function, and wound healing.…”
Section: ■ Introductionmentioning
confidence: 99%